2017
DOI: 10.1038/s41467-017-00404-y
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome-interacting factors directly suppress MIR156 expression to enhance shade-avoidance syndrome in Arabidopsis

Abstract: Plants have evolved a repertoire of strategies collectively termed the shade-avoidance syndrome to avoid shade from canopy and compete for light with their neighbors. However, the signaling mechanism governing the adaptive changes of adult plant architecture to shade is not well understood. Here, we show that in Arabidopsis, compared with the wild type, several PHYTOCHROME-INTERACTING FACTORS (PIFS) overexpressors all display constitutive shade-avoidance syndrome under normal high red to far-red light ratio co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
166
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(174 citation statements)
references
References 58 publications
(74 reference statements)
7
166
0
1
Order By: Relevance
“…This phenomenon is widely conserved, including legumes such as alfalfa (Aung et al ., ; Gao et al ., ) and soybean (Sun et al ., ). Furthermore, Xie and collaborators recently showed that microRNA156 genes are downregulated in response to shade, resulting in the upregulation of SPL genes and early flowering in Arabidopsis (Xie et al ., ). We hypothesized that shade regulation of microRNA156 could also be part of the response to shade in alfalfa.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This phenomenon is widely conserved, including legumes such as alfalfa (Aung et al ., ; Gao et al ., ) and soybean (Sun et al ., ). Furthermore, Xie and collaborators recently showed that microRNA156 genes are downregulated in response to shade, resulting in the upregulation of SPL genes and early flowering in Arabidopsis (Xie et al ., ). We hypothesized that shade regulation of microRNA156 could also be part of the response to shade in alfalfa.…”
Section: Resultsmentioning
confidence: 97%
“…Our results strongly suggest that the downregulation of msSPL3 is an important mechanism to delay flowering in alfalfa grown in shade conditions (Figures and S6; Table ). In Arabidopsis, shade produces high PIF activity, which represses mir156 expression, leading to high levels of SPL mRNAs, high FT levels and accelerated flowering (Xie et al ., ). Here we found that despite the fact that the same orthologs seem to be involved in alfalfa, the opposite modulation of msSPL3 in response to shade has diversified, consistent with the life history of alfalfa.…”
Section: Discussionmentioning
confidence: 97%
“…Our previous study showed that compared with their counterparts grown under WL conditions, EOD-FR-treated plants had significantly upregulated expression of SPL3, SPL4, and SPL5 (Xie et al, 2017). To examine whether EOD-FR treatment also affects accumulation of the proteins encoded by these SPL genes, we generated p35S::rSPL3-HA and p35S::rSPL4-HA transgenic plants.…”
Section: Spl3/4/5 Promote Flowering In Response To Shade By Upregulatmentioning
confidence: 99%
“…In addition, several atypical basic helix-loop-helix transcription factors named LONG HYPOCOTYL IN FAR-RED1 (HFR1), PHYTOCHROME RAPIDLY REGULATED1 (PAR1), and PAR2, have been identified as negative regulators that balance SAS through the formation of non-DNA-binding heterodimers (Lorrain et al, 2008;Hornitschek et al, 2009;Galstyan et al, 2011;Hao et al, 2012). We recently showed that the levels of PIF proteins rapidly increase in response to simulated shade conditions, and that several PIF proteins (PIF1, PIF3, PIF4, and PIF5) can directly bind to the promoters of several MIR156 genes and repress their expression, leading to concomitant elevated expression of the downstream SQUAMOSA-PROMOTER BINDING PROTEIN-LIKE (SPL) family genes and enhanced SAS (Xie et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Circadian rhythm is also integrated into this system as shown recently for miR156. Phytochrome Interacting Factors (PIFs) directly interact with G-box motifs of MIR156 and repress their expression to enhance shade avoidance response in plants, phenotypes of which mimic miR156 knock down (Xie et al, 2017).…”
Section: Transcription Of Mir Genes and Its Regulationmentioning
confidence: 99%